2023
DOI: 10.3390/s23062929
|View full text |Cite
|
Sign up to set email alerts
|

Lettuce Production in Intelligent Greenhouses—3D Imaging and Computer Vision for Plant Spacing Decisions

Abstract: Recent studies indicate that food demand will increase by 35–56% over the period 2010–2050 due to population increase, economic development, and urbanization. Greenhouse systems allow for the sustainable intensification of food production with demonstrated high crop production per cultivation area. Breakthroughs in resource-efficient fresh food production merging horticultural and AI expertise take place with the international competition “Autonomous Greenhouse Challenge”. This paper describes and analyzes the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 54 publications
0
8
0
1
Order By: Relevance
“…Here, in direct sunlight, both 99th and 98th percentile RMSE_B values are less than 7 cm, which appears to be better than the findings of Neupane et al [ 44 ]. Petropoulou et al deployed a RealSense camera in their study for estimating lettuce growth with an R 2 of 0.976 [ 18 ]. In this study, the okra FPH and IPH were found to be significantly correlated, with R 2 values for the 98th and 99th percentiles of 0.9729 ( Figure 7 ) and 0.9711, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, in direct sunlight, both 99th and 98th percentile RMSE_B values are less than 7 cm, which appears to be better than the findings of Neupane et al [ 44 ]. Petropoulou et al deployed a RealSense camera in their study for estimating lettuce growth with an R 2 of 0.976 [ 18 ]. In this study, the okra FPH and IPH were found to be significantly correlated, with R 2 values for the 98th and 99th percentiles of 0.9729 ( Figure 7 ) and 0.9711, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…IoT facilitates remote monitoring and operation, requires minimal energy, automatically records large volumes of data, may be controlled remotely, and improves efficiency [ 15 , 16 , 17 ]. IoT-based farming can promote agricultural automation by equipping it with a sensor network [ 18 ], which could increase crop yield and reduce operating costs [ 19 ]. During the crop growth period, observations and analyses can be conducted even in poor weather conditions when routine checks are not feasible.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementing a more energy-efficient approach to humidity regulation can significantly reduce the energy consumption associated with agriculture, which currently amounts to as much as 1872 trillion Btu per year in the United States . In recent years, new technologies including functional greenhouse covers and Internet of Things have been developed to enable energy-independent, labor-independent, and high-yield greenhouses. Major efforts have been devoted to intelligent photovoltaic systems that regulate solar radiation, generate energy, and control temperature. , However, advanced solutions for humidity regulation have not been explored in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, plant factories must track the fresh weight of crops because they are cultured in bulk in the system. This is because the owner should meet the ordered quantity and quality, including certain sizes and weights, and have a specific date of shipping when an indoor farm is commercialized ( Petropoulou et al., 2023 ). A delay in shipment is one of the most severe problems in commercial indoor farming.…”
Section: Introductionmentioning
confidence: 99%